2006
DOI: 10.1016/j.euromechsol.2006.02.006
|View full text |Cite
|
Sign up to set email alerts
|

A predictive mechano-biological model of the bone-implant healing

Abstract: The quality of the fixation orthopaedic implant to its surrounding bone determines its clinical longevity. Up to 20% of hip replacement operations are currently revisions for aseptic loosening. While this fixation quality is determined primarily by the bone and tissue anchoring the implant, conditions influencing bone growth in the early post-operative period include the surgical technique and coupled mechanical and biochemical factors. The aim of the study was to propose an original mechano-biological formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 19 publications
0
43
0
1
Order By: Relevance
“…Although the interest of these works is unquestionable, it is the authors' opinion that mechanobiological models in which specific biological processes coupled with mechanics are modelled together with their influence on the structure and mechanical properties of tissues constitute a richer source of information for the understanding of many problems in biomedical sciences. However, it is a field where not many works exist, being possible to find only a few addressed 4 A c c e p t e d m a n u s c r i p t to the study of peri-implant endosseous healing (Geris et al, 2004;Andreykiv et al, 2005;Ambard and Swider, 2006;Liu and Niebur, 2007). We would like to remark that all these works consider in different depth several aspects of the biology of bone healing around implants, but they do not contemplate, or they do it in a superficial manner, the effect of the implant surface topography on biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the interest of these works is unquestionable, it is the authors' opinion that mechanobiological models in which specific biological processes coupled with mechanics are modelled together with their influence on the structure and mechanical properties of tissues constitute a richer source of information for the understanding of many problems in biomedical sciences. However, it is a field where not many works exist, being possible to find only a few addressed 4 A c c e p t e d m a n u s c r i p t to the study of peri-implant endosseous healing (Geris et al, 2004;Andreykiv et al, 2005;Ambard and Swider, 2006;Liu and Niebur, 2007). We would like to remark that all these works consider in different depth several aspects of the biology of bone healing around implants, but they do not contemplate, or they do it in a superficial manner, the effect of the implant surface topography on biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the implant osseointegration experiments (Søballe 1993) that were used by Prendergast et al (1997) to develop their model, Ambard & Swider (2006) proposed a bioregulatory model of bone implant healing, where the migration of osteoblasts towards the implant surface is mediated both by the presence of an osteogenic growth factor and the local matrix density. Geris et al (2008a) started from the model of Bailón-Plaza & van der Meulen (2001) and introduced key aspects of healing such as angiogenesis and directed cell migration.…”
Section: Bone Regeneration (A ) Biology Of Bone Regenerationmentioning
confidence: 99%
“…With our canine experimental model, histological studies showed that several types of distribution patterns of neo-formed bone could be found, and all involved peaks in the drill-hole zone and at the implant surface (Vestermark et al, 2004;Ambard and Swider, 2006;Swider et al, 2010). Unfortunately, studies about the neo-vascularization and the activity of endothelial cells have not been carried out yet.…”
Section: Discussionmentioning
confidence: 99%
“…While some updating could be made with bony tissue (Ambard and Swider, 2006), convective and diffusive properties of vascular tissue were poorly known especially in bone neovascularization. This showed that mixed theoretical-experimental studies, in-vitro and in-vivo, could be planned to reinforce the model relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation